Tomato salt tolerance mechanisms and their potential applications for fighting salinity: A review - Guo, Meng; Wang, Xin-Sheng; Guo, Hui-Dan; Bai, Sheng-Yi; Khan, Abid; Wang, Xiao-Min; Gao, Yan-Ming; Li, Jian-She (Frontiers in Plant Science, 2022)
One of the most significant environmental factors affecting plant growth, development and productivity is salt stress. The damage caused by salt to plants mainly includes ionic, osmotic and secondary stresses, while the plants adapt to salt stress through multiple biochemical and molecular pathways. Tomato (Solanum lycopersicum L.) is one of the most widely cultivated vegetable crops and a model dicot plant. It is moderately sensitive to salinity throughout the period of growth and development. Biotechnological efforts to improve tomato salt tolerance hinge on a synthesized understanding of the mechanisms underlying salinity tolerance. This paper provides a comprehensive review of major advances on the mechanisms controlling salt tolerance of tomato in terms of sensing and signaling, adaptive responses, and epigenetic regulation. Additionally, we discussed the potential application of these mechanisms in improving salt tolerance of tomato, including genetic engineering, marker-assisted selection, and eco-sustainable approaches.